Performance of a damage-protected beam?column subassembly utilizing external HF2V energy dissipation devices. - Rodgers, Geoffrey W. (Earthquake engineering & structural dynamics.)
Ductile-jointed connections, which generally require some form of supplementary energy dissipation to alleviate displacement response, typically employ mild steel energy dissipation devices. These devices run the risk of low-cycle fatigue, are effective only for peak cycles that exceed prior displacements, are prone to buckling, and may require replacement following an earthquake. This study presents an experimental investigation employing an alternative to mild steel: a high force-to-volume (HF2V) class of damper-based energy dissipation devices. Tests are performed on a near full-scale beam?column joint subassembly utilizing externally mounted compact HF2V devices. Two configurations are considered: an exterior joint with two seismic beams and one gravity beam framing into a central column, and a corner joint with only one seismic beam and one gravity beam framing into a column. Quasi-static tests are performed to column drifts up to 4%. The experiments validate the efficacy of the HF2V device concept, demonstrating good hysteretic energy dissipation, and minimal residual device force, allowing ready re-centring of the joint. The devices dissipate energy consistently on every cycle without the deterioration observed in the yielding steel bar type of devices. The effectiveness of the HF2V devices on structural hysteretic behavior is noted to be sensitive to the relative stiffness of the anchoring elements, indicating that better efficiency would be obtained in an embedded design.